Implementasi Pemanfaatan Sumber Radiasi Pengion pada Ruang CT Scan ditinjau berdasarkan Peraturan BAPETEN No. 4 tahun 2020 di Instalasi Radiologi Rumah Sakit type B di Wilayah Kabupaten Sumedang - Anggraeni, Leny; Nuramdiani, Dian (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: Occupational safety and health (OSH) management is the main factor in hospital services, which aims to control and minimize potential dangers due to radiation. One of the evaluations used is the implementation of OSH management requirements based on the Republic of Indonesia Ministry of Health Regulation No. 1014 of 2008 and Bapeten regulation no. 4 of 2020. The aim of this research was to determine the extent of implementation of OSH management in terms of completeness of management requirements, radiation protection, room design and personal protective equipment (PPE) implemented in Radiology Department in hospital type B, Sumedang Regency.Methods: This research was a descriptive qualitative by conducting direct observations, interviews and documentation.Results: The results of the research on the design of the room without ventilation outside the CT Scan room, this aims to minimize the dose of scattered radiation that comes out, decentralization and good air circulation, has warning signs and directions for radiation danger areas, the radiation protection equipment is quite complete. Implementation of radiation management has been carried out, but not completely, there is no health monitoring at the end of the work period and upon termination of work. Radiation safety verification has been carried out periodically, quality control is only carried out externally, so it does not meet standards, internal quality control cannot be carried out because there is no survey meter.Conclusions: This research was conducted in Radiology Department room in August 2023, the results showed that in the CT Scan room there was no air ventilation, there was radiation dose monitoring for staff, overall, Radiology Installation hospital type B in Sumedang Regency area had implemented occupational safety and health.